Drivers of entrepreneurial orientation and innovation capabilities in African Internet start-ups - Onwu, Ekenedilichukwu Gilbert (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.